Comparative analysis of calcified soft tissues revealed shared deregulated pathways - Ibragimova, Aminat Guseynovna; Stanishevskiy, Yaroslav Mikhailovich; Plakkhin, Alexey Mikhaylovich; Zubko, Alexandr Vladimirovich; Darvish, Nidal Akhmedovich; Koassary, Anton Karenovich; Shindyapina, Anastasia V. (Frontiers in Aging Neuroscience, 2023)
Calcification of soft tissues is a common age-related pathology that primarily occurs within vascular tissue. The mechanisms underlying pathological calcification in humans and tissue specificity of the process is still poorly understood. Previous studies examined calcified tissues on one-to-one basis, thus preventing comparison of deregulated pathways across tissues. This study aimed to establish common and tissue-specific changes associated with calcification in aorta, artery tibial, coronary artery and pituitary gland in subjects from the GTEx dataset using RNA sequencing and histological data generated by consortium from a few hundred subjects. We identified calcification deposits in 28 (6.5%) aortas, 121 (20%) artery tibials, 54 (43%) coronary arteries and 24 (8%) pituitary glands of GTEx subjects. We found an age-dependent increase of calcification cases in all vascular tissues, but not in pituitary. Subjects with calcification in the artery tibial were more likely to have calcification in the coronary artery (OR=2.56, p-value=6.3e-07). Markers of calcification previously established in preclinical and in vitro studies, e.g. BMP2 and RUNX2, were deregulated in the calcified tibial and coronary arteries, confirming the relevance of these genes to human pathology. Differentially expressed genes associated with calcification poorly overlapped across tissues suggesting tissue-specific nuances in mechanisms of calcification. Nevertheless, calcified arteries unanimously down-regulated pathways of intracellular transport and up-regulated inflammatory pathways suggesting these as universal targets for pathological calcification. PD-1 and PD-L1 genes were up-regulated in calcified tissues but not in the blood of the same subjects, suggesting that localized inflammation contributes to pathological calcification. Pathological calcification is a prevalent disease of aging that shares little changes in expression in individual genes across tissues. However, our analysis suggests that it potentially can be targeted by alleviating local inflammation of soft tissues.